Soccer Injuries in Players Aged 7 to 12 Years: A Descriptive Epidemiological Study Over 2 Seasons - Rössler, Roland; Junge, Astrid; Chomiak, Jiří; Dvorak, Jiri; Faude, Oliver (American journal of sports medicine, 2016)
BACKGROUND: As part of a risk-management approach, sound epidemiological data are needed to develop prevention programs. A recent review on soccer injuries of players younger than 19 years concluded that prospective data concerning children are lacking. PURPOSE: To analyze the incidence and characteristics of soccer injuries in children aged 7 to 12 years. STUDY DESIGN: Descriptive epidemiological study. METHODS: The present survey was a prospective descriptive epidemiological study on soccer injuries over 2 seasons in the Czech Republic and Switzerland. Exposure of players during training and match play (in hours) and injury data were reported by coaches via an Internet-based registration system. Location, type, and severity of injuries were classified according to an established consensus. Injury characteristics are presented as absolute numbers and injury incidence rates (injuries per 1000 hours of soccer exposure). An injury was defined as any physical complaint sustained during a scheduled training session or match play resulting in at least 1 of the following: (1) inability to complete the current match or training session, (2) absence from subsequent training sessions or matches, and (3) injury requiring medical attention. RESULTS: In total, 6038 player-seasons with 395,295 hours of soccer exposure were recorded. The mean (±SD) age of the players was 9.5 ± 2.0 years, and 3.9% of the participants were girls. A total of 417 injuries were reported. Most (76.3%) injuries were located in the lower limbs, with 15.6% located in the upper limbs. Joint and ligament injuries comprised 30.5%, contusions 22.5%, muscle and tendon injuries 18.5%, and fractures and bone injuries 15.4% of all injuries; 23.7% of injuries led to more than 28 days of absence from sport participation. The overall injury incidence was 0.61 (95% CI, 0.53-0.69) injuries per 1000 hours of soccer exposure during training sessions and 4.57 (95% CI, 4.00-5.23) during match play. Injury incidence rates increased with increasing age. CONCLUSION: The observed injury incidences were lower compared with studies in youth players. Children showed a relatively high proportion of fractures and bone stress and of injuries to the upper limbs. CLINICAL RELEVANCE: The study provides an evidence base for injury incidence rates and injury characteristics in children's soccer. These data are the basis to develop an age-specific injury-prevention program.
Keywords: fotbal; Seasons; fyzikální vyšetření; Soccer; Contusions; Incidence; mladiství; Česká republika; mužské pohlaví; Athletic Injuries; incidence; Program Evaluation; hodnocení programu; Prospective Studies; Fractures, Bone; zhmoždění; Sprains and Strains; Czech Republic; dítě; Child; Physical Examination; Child, Preschool; Tendon Injuries; ženské pohlaví; Switzerland; Humans; předškolní dítě; prospektivní studie; fraktury kostí; poranění šlachy; distorze a distenze; Švýcarsko; Warm-Up Exercise; sportovní úrazy; Female; roční období; Adolescent; výzkumný projekt; Research Design; zahřívací cvičení; lidé; Male